Religion and global peace: the instrumental value of religion - Malik, Mohammad Manzoor; Kayadibi, Saim (2010)
Religious believers claim their religions are peaceful and genuine believers are peacekeepers and peacemakers. In substantiating justification to their claim, they very often refer to religious scriptures. Yet, on the contrary, their claim is confronted by an opposite claim: many wars were fought and are being fought in the name of religion; and a great deal of violence can be ascribed to the religious believers. In addition, religious scriptures and history of religions do attest, to a certain extent, permissibility of using physical offence or defence. As a result, a question arises: Is the violence credited to religious believers, due to religions? Or is it because of certain secular causes in which religious texts get invoked very often? In responding to the question, the study relied on the theoretical criticism and justification. The study argued that religions, considering their historical inception, are fundamentally aimed at attaining holistic peace for their immediate subjects and subsequent followers, both spiritually and physically. The approval of violence attributed to religions is mainly relevant to safeguarding believers’ existential safety and prosperity; therefore, maintaining and securing a safe human existential condition plays the rationale and stimulus for the violence which may be termed as religious, but in fact, is not so. Economical, political, and social reasons amount to the main reasons of conflict in which any community, in certain conditions including a religious community, could engage. In case of a religious community, the struggle caused by purely secular reasons use religion as an instrument for defiance, solidarity, and cohesion. In an absence of religion or ineffective appeal of religion or sectarian violence within the followers of the same religion, the combating factions very well use other appealing catchwords such as race, colour, tribe, nation, language, ethnicity, etc. The study by referring to major religions of the world generally and Islam particularly, lastly argued that in contributing to build global peace, religious believers can plausibly turn to primary peaceful intentions of the religions, if they are provided with a feasible atmosphere .